Dystrophin Dp71 in PC12 cell adhesion - Enríquez-Aragón, Jose Arturo (Lippincott Williams & Wilkins, 2005)
Previously, we reported that PC12 cells with decreased Dp71 expression (antisense-Dp71 cells) display deficient nerve-growth-factor-induced neurite outgrowth. In this study, we show that disturbed neurite outgrowth of antisense-Dp71 cells is accompanied by decreased adhesion activity on laminin, collagen and fibronectin. In wild-type cells, the immunostaining of Dp71 and _1-integrin overlaps in the basal area contacting the substrate, but staining of both proteins decrease in the antisense-Dp71 cells. Morphology of antisense-Dp71 cells at the electron microscopic level is characterized by the lack of filopodia, cellular projections involved in adhesion. Our findings suggest that Dp71 is required for the efficient PC12 cell attachment to b1-integrin-dependent substrata and that decreased adhesion activity of the anti-sense-Dp71 cells could determine their deficiency to extend neurites.